Variabilidade espacial e temporal do estresse térmico sobre o banco de Abrolhos, Atlântico Sul - Monteiro, Natiely Priscila Paiva (2021)
Thermal stress (ET), which is associated with a change in temperature that can be severe enough to cause unfavorable or even lethal conditions to aquatic organisms, populations, community structure, or ecosystems, has also been associated with coral bleaching. In this sense, it is essential to monitor the spatial-temporal variability of seawater temperature everywhere, including in the Abrolhos Bank region. Coral Reef Watch (CRW) provides ex-situ daily sea surface temperature measurements for this area. Although TSM is an essential source of data, especially in the absence of in situ measurements, it is necessary to evaluate this measurement's spatial-temporal representativeness compared to those taken in the field. Thus, it will be possible to assess whether the thermal stress indicated by CRW is representative, i.e., it is similar to that estimated from on-site seawater temperature measurements. This study's general objective is to evaluate the space-time representativeness of the temperature measurements and thermal stress estimates obtained in situ and ex-situ on the Abrolhos Bank. The results obtained showed that the thermal pattern observed in Abrolhos is characterized by a heating-cooling cycle, with the peak temperature observed at the end of the summer beginning of autumn. When comparing the alerts generated by a single point temperature series by CRW with in situ measurements obtained at different depths and locations, it was seen that the spatial extrapolation is not valid. The comparison between in situ and CRW data showed that, both in the alert's duration and intensity, the differences between the ex-situ temperature estimate and the temperature that acts on the corals could be considerable. These differences partly reflect the vertical stratification on the Abrolhos Bank in the critical months of liquid heat flow towards the ocean (end of the rainy season and beginning of the dry season). Temperature measurements of the deep corals and the outer bow showed values below the Maximum Mean Monthly Temperature, preventing thermal stress on the corals. In the dry season, the thermal homogeneity of the water column occurs. Finally, for coastal and shallow reefs (but relatively distant from the coast), the bleaching alerts compare with each other. However, this does not mean that the whitening will effectively occur at the predicted level. It needs to be evaluated punctually and individually since physical-chemical processes can affect them distinctly in different locations.